Pendekatan Belajar Melalui Bermain dan Tahap Pertuturan Kanak-Kanak Prasekolah: Kerangka Konseptual - Thavandran, Amala; Che Hussain, Siti Rehani (Selangor Humaniora Review, 2019)
In this study, researchers used the learning through play approach to identify the effectiveness of improving the speech levels of preschool children. Learning through play is an effective teaching and learning technique for children. Through this technique, children get pleasure and satisfaction in a lesson to be delivered. In addition, by playing, children will master the development and physical skills and mastery of language in terms of vocabulary and grammar rules. Through literature review and theoretical review, a built-in conceptual framework for this study’s foundation was developed. The conceptual framework of this study is based on Piaget’s Cognitive Theory and Chomsky’s Mentalist Theory in identifying the use of learning through play approaches in teaching and learning to improve the speech level of preschool children.